2022
DOI: 10.3389/fphar.2022.970280
|View full text |Cite
|
Sign up to set email alerts
|

Dietary stilbenes as modulators of specific miRNAs in prostate cancer

Abstract: Accumulated experimental data have suggested that natural plant products may be effective miRNA-modulating chemopreventive and therapeutic agents. Dietary polyphenols such as flavonoids, stilbenes, and lignans, among others, have been intensively studied for their miRNA-mediated cardioprotective, antioxidant, anti-inflammatory and anticancer properties. The aim of this review is to outline known stilbene-regulated miRNAs in cancer, with a special focus on the interplay between various miRNAs and MTA1 signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 127 publications
0
5
0
Order By: Relevance
“…In addition, PTE possesses various pharmacological activities, including anticancer, antiinflammatory, and antioxidant activities. [41][42][43] We measured intracellular ROS levels in Raw 264.7 macrophages using DCHF as a fluorescent probe. Our results showed that ROS levels were inhibited in the PTE-treated group compared with the LPStreated group (ESI Fig.…”
Section: Pte Treatment Inhibits Macrophage Pyroptosis In Vivo and In ...mentioning
confidence: 99%
“…In addition, PTE possesses various pharmacological activities, including anticancer, antiinflammatory, and antioxidant activities. [41][42][43] We measured intracellular ROS levels in Raw 264.7 macrophages using DCHF as a fluorescent probe. Our results showed that ROS levels were inhibited in the PTE-treated group compared with the LPStreated group (ESI Fig.…”
Section: Pte Treatment Inhibits Macrophage Pyroptosis In Vivo and In ...mentioning
confidence: 99%
“…Metastasis-associated protein 1 (M overexpressed in PCa, especially in bone metastatic lesions, and is related to d expression of E-cadherin through cathepsin B (CTSB), leading cells to EMT [188 was found to be positively associated with MTA1 and contribute to reducing Eexpression [189]. Dietary polyphenols such as flavonoids and stilbenes, i resveratrol, are related to inhibition of miR-22 and the oncogenic MTA1-a miRNAs miR-17 and miR-34a [190,191]. Pterostilbene, along with res downregulates miR-17-5p and miR-106a-5p, miRNAs that target tumor su phosphatase and tensin homolog (PTEN) [192,193].…”
Section: Mirnas As Potential Therapeutic Targetsmentioning
confidence: 99%
“…miR-22 was found to be positively associated with MTA1 and contribute to reducing E-cadherin expression [ 189 ]. Dietary polyphenols such as flavonoids and stilbenes, including resveratrol, are related to inhibition of miR-22 and the oncogenic MTA1-associated miRNAs miR-17 and miR-34a [ 190 , 191 ]. Pterostilbene, along with resveratrol, downregulates miR-17-5p and miR-106a-5p, miRNAs that target tumor suppressor phosphatase and tensin homolog (PTEN) [ 192 , 193 ].…”
Section: Mirnas As Potential Therapeutic Targetsmentioning
confidence: 99%
“…MTA1 is responsible for deacetylating PTEN, an important tumor suppressor protein, thereby inhibiting its expression. Pterostilbene reduced MTA1-dependent cell survival and metastasis in prostate cancer by inhibiting MTA1 expression, disrupting the MTA1-histone deacetylase complex, and restoring PTEN expression ( Dhar et al, 2016 ; Levenson, 2022a ; Levenson, 2022b ; Kocabas and Sanlier, 2023 ). In hepatocellular carcinoma, Pterostilbene decreased MTA1 expression and HDAC1 activity, disrupting the MTA1/histone deacetylase complex and leading to restored PTEN acetylation and subsequent induction of apoptosis in cancer cells ( Qian et al, 2018 ).…”
Section: Epigenetic Regulation Of Stilbenes and Their Derivatives——po...mentioning
confidence: 99%
“…Examples include Resveratrol (RSV), Pterostilbene (PTE), and their dimers, such as (±)-trans-δ-vinifera ( Giacomini et al, 2016 ; Kluska et al, 2023 ). They function as antioxidants and anticancer agents, modulating epigenetic marks that impact disease progression, particularly in terms of DNA methylation and histone modification ( Ganguly et al, 2021 ; Levenson, 2022a ; Sukocheva et al, 2022 ), which, in turn, can influence gene expression patterns and promote or hinder disease progression.…”
Section: Introductionmentioning
confidence: 99%